(untitled) (LACCEI, 2024)
Mining is the reason for great technological advances, which through science make it possible to manufacture electronic equipment. These devices, after their useful lifetimes, are discarded, becoming part of the millions of tons of electronic scrap produced. This massive mountain of electronic scrap has the potential for gold extraction through an acid-leaching process for subsequent recovery with solvents or chemical adsorption agents. However, a series of materials have been postulated, including carbons, gels, and compounds extracted from vegetable matter, to manufacture adsorbent materials, giving a second use to organic matter residues, which are an interesting alternative on the way. towards a sustainable industrial process. This review presents alternatives of materials such as barley, rice, orange, persimmon, and apricot, capable of being transformed into adsorbent materials that achieved a 99% recovery in an estimated contact time of 0.5 to 100 hours. Since Peru is a country with enormous agricultural potential, these new applications could increase the reach of this market internationally, favoring the consolidation of sustainable technologies.